2023
DOI: 10.1038/s41598-023-38267-7
|View full text |Cite
|
Sign up to set email alerts
|

Fructooligosaccharide and Bacillus subtilis synbiotic combination promoted disease resistance, but not growth performance, is additive in fish

Abstract: Species diversification from major to minor carps for their sturdiness and initial higher growth, and also a quest for antibiotic-free aqua farming in the subcontinent, mandates search for and evaluation of alternatives. An experiment was performed to investigate the potential of fructooligosaccharide (FOS) and Bacillus subtilis (BS) (alone or as synbiotics) in promoting growth and immunity against infections in Labeo fimbriatus fingerlings. Six iso-nitrogenous and iso-lipidic diets containing combinations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…For example, ref. [ 54 ] found that the levels of protein, albumin, and A:G decreased in fish infected with bacterial isolates, while the levels of NBT and bactericidal activity showed a constant decrease. This suggests that bacterial isolates can have a negative impact on the humoral immunity of fish [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, ref. [ 54 ] found that the levels of protein, albumin, and A:G decreased in fish infected with bacterial isolates, while the levels of NBT and bactericidal activity showed a constant decrease. This suggests that bacterial isolates can have a negative impact on the humoral immunity of fish [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mixture comprising live microorganisms and substrates selectively utilized by host microorganisms was an effective dietary symbiotic supplementation, as evaluated by Singh et al (2019) [70]. Bacillus circulans PB7 (BCPB7) and FOS were proposed to improve the immune response of juveniles Labeo rohita under persistent stress to low pH for 60 days.…”
Section: Immune Responsementioning
confidence: 99%